2008
DOI: 10.1002/bem.20434
|View full text |Cite
|
Sign up to set email alerts
|

Changes in human EEG alpha activity following exposure to two different pulsed magnetic field sequences

Abstract: The present study investigates the effects of a weak (+/-200 microT(pk)), pulsed, extremely low frequency magnetic field (ELF MF) upon the human electroencephalogram (EEG). We have previously determined that exposure to pulsed ELF MFs can affect the EEG, notably the alpha frequency (8-13 Hz) over the occipital-parietal region of the scalp. In the present study, subjects (n = 32) were exposed to two different pulsed MF sequences (1 and 2, used previously) that differed in presentation rate, in order to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Some relevant studies to which our results can be compared are those of Cook et al [19]- [20] which employed exposures that bear some spectral resemblance to those employed here (pulsed ELF exposures but with homogeneous exposure properties), and they reported both increases and decreases of alpha activity during and shortly after exposure. In addition Stevens reported a decrease of alpha activity after exposure to weak magnetic fields [28].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Some relevant studies to which our results can be compared are those of Cook et al [19]- [20] which employed exposures that bear some spectral resemblance to those employed here (pulsed ELF exposures but with homogeneous exposure properties), and they reported both increases and decreases of alpha activity during and shortly after exposure. In addition Stevens reported a decrease of alpha activity after exposure to weak magnetic fields [28].…”
Section: Discussionmentioning
confidence: 81%
“…Due to the difference in spectral content of the ELF fields (compared to RF) it is possible that these fields may interact differently, if at all, with the human EEG. EEG studies with exposures that share some resemblance to the GSM-ELF fields have shown changes in resting brain activity (albeit inconsistently), thereby justifying further investigation with mobile phone-like exposure conditions [19]- [21].…”
mentioning
confidence: 99%
“…25,33,34 Many of the studies from 1985 to 2005, gathered in a review article, illustrated the effect of the use of large spread spectrum of PEMF doses on decreasing headache activity. 17 Although most of these research studies had no control or comparison group, or had very brief follow-up periods and uncompleted reports of dosimeter.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was effective in reducing muscle soreness in marathon runners [4]. The effects of PMF stimulus on the autonomic nervous system and frontal lobe activities were evaluated in several papers [5,6]. Shupak et al showed that exposure to PMF stimulus has a potential analgesic effect with increased pain thresholds [3].…”
Section: Introductionmentioning
confidence: 99%